6-Amino-2-ammoniotoluene-4-sulfonate - Huo, L.H.; Ng, S.W.; Zain, Sharifuddin Md; Gao, S.; Xu, S.X. (International Union of Crystallography, 2005)
2,6-Diaminotoluene-4-sulfonic acid exists in the zwitterionic form as 2-amino-6-ammoniotoluene-4-sulfonate, C 7H 10N 2O 3S; the molecule features a C-N amino bond [1.372 (3) Å] which is significantly shorter than the C-N ammonio bond [1.473 (3) Å]. Neighbouring molecules are linked by extensive hydrogen bonds into a three-dimensional network structure. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.